Corporate Governance, Investment in Research and Development and Company Performance: A Data Envelopment Analysis Approach Based on Data from a Developing Country - Setayesh, Mohammad-Hossein; Rezaie, Gholamreza; Kazemnezhad, Mostafa (International Journal of Economics and Financial Issues, 2016)
The aim of this paper is to investigate the role of investment in research and development (R&D) in relationship between corporate governance and company performance in the Tehran Stock Exchange. In this regard, ownership concentration and debt ratio were used as the criteria for corporate governance. The statistical population included all companies listed in Tehran Stock Exchange, 161 of which were selected as the statistical sample and investigated from 2004 until 2014. The statistical regression analysis of mixed data in the Baron and Kenny model (1986) and hierarchical regression analysis were employed to test the research hypotheses. The results indicated that corporate governance was a factor influencing company performance and R&D activities. The results also indicated that investment in R&D improved company performance. Furthermore, the research evidence showed a minor role for the R&D investment variable in mediating the relationship between corporate governance and company performance, and thus could not play a moderating role in this relationship. Keywords: Ownership Concentration, Debt Ratio, Company Performance, Investment in R&D JEL Classifications: C61, G30, M41